2014
DOI: 10.1073/pnas.1420159112
|View full text |Cite
|
Sign up to set email alerts
|

Dual-specificity phosphatase 5 regulates nuclear ERK activity and suppresses skin cancer by inhibiting mutant Harvey-Ras (HRas Q61L )-driven SerpinB2 expression

Abstract: Ectopic expression of dual-specificity phosphatase 5 (DUSP5), an inducible mitogen-activated protein (MAP) kinase phosphatase, specifically inactivates and anchors extracellular signal-regulated kinase (ERK)1/2 in the nucleus. However, the role of endogenous DUSP5 in regulating the outcome of Ras/ERK kinase signaling under normal and pathological conditions is unknown. Here we report that mice lacking DUSP5 show a greatly increased sensitivity to mutant Harvey-Ras (HRas Q61L )-driven papilloma formation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 34 publications
8
81
0
Order By: Relevance
“…S1B) and DUSP5 expression (Fig. 1C), suggesting that DUSP5 may be responsible for the nuclear accumulation and dephosphorylation of ERK (21,22). In agreement with this hypothesis, Dusp5 deletion both reduced the N:C ERK ratio and elevated nuclear p-ERK levels ( Fig.…”
Section: Significancesupporting
confidence: 80%
See 4 more Smart Citations
“…S1B) and DUSP5 expression (Fig. 1C), suggesting that DUSP5 may be responsible for the nuclear accumulation and dephosphorylation of ERK (21,22). In agreement with this hypothesis, Dusp5 deletion both reduced the N:C ERK ratio and elevated nuclear p-ERK levels ( Fig.…”
Section: Significancesupporting
confidence: 80%
“…We have previously demonstrated that DUSP5 causes both nuclear accumulation and dephosphorylation of ERK in MEFs when stimulated with the phorbol ester TPA (22). These localized effects were revealed using confocal and high-content microscopy (HCM) (22).…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations